Characteristics and Outcomes of Chinese Children With Advanced Stage Anaplastic Large Cell Lymphoma: A Single-Center Experience - Zhang, Yu-Tong; Wang, Li-Zhe; Chang, Jian (Frontiers in Oncology, 2022)
Purpose To evaluate the clinical characteristics and treatment outcomes of Chinese children with advanced stage anaplastic large cell lymphoma (ALCL) who were treated with the low-intensity APO regimen. Methods Clinical data from children newly diagnosed with advanced stage ALCL and treated with the APO regimen were reviewed. Results Altogether 22 eligible patients with advanced stage ALCL were recruited in this study. 18 (81%) patients achieved complete response (CR) after the initial induction, and 4 experienced relapse. Among patients with relapsed or refractory ALCL, CR was achieved in 3 (50%) who received the BFM95 R3/R4 regimen. Besides, 2 patients received the targeted therapy with crizotinib and were still alive. The 5-year OS and EFS rates were 82±8.7% and 68.2±9.4%%, respectively. According to our results, the elevated LDH level and bone marrow involvement were identified as the poor prognostic factors for EFS (p=0.035 and 0.048, respectively). During APO treatment, only 23% patients experienced grade 3-4 hematologic toxicity. Conclusions In this study, bone marrow involvement and elevated serum LDH levels were identified as the poor prognostic factors for EFS. In resource-limited regions, patients with advanced stage ALCL can also achieve comparable outcomes to those in high-income regions, and the BFM95 R3/R4 regimen can take the role of salvage treatment for patients with relapsed or refractory disease. Nonetheless, new therapeutic strategy is still needed.